Exploring the Interplay between Business Economics and Global Trade - Nhung, Tienne (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
This study explores the interplay between Business Economics and global trade, focusing on how firms apply economic principles to navigate international markets. The primary aim is to understand how economic policies, risk management, and strategic decision-making processes influence global trade strategies. Utilizing a qualitative research methodology, the study involves in-depth interviews with business economists, trade experts, and senior executives from multinational corporations. Data collection centers on participants’ experiences and insights regarding the impact of economic policies, risk management strategies, and decision-making processes in global trade contexts. Thematic analysis of the interview data reveals that firms actively use Business Economics to adapt to changing trade policies, manage risks such as currency fluctuations and geopolitical instability, and optimize their market entry and pricing strategies. The study highlights that businesses leveraging economic models and principles are better positioned to respond to external changes, mitigate risks, and capitalize on growth opportunities in the global market. These findings underscore the critical role of Business Economics in shaping effective global trade strategies and offer valuable insights for firms seeking to enhance their international operations.